Negotiating non-normative identities: gender nonconforming Malaysian muslims on instagram - Kamaruzaman, Nur Atirah (SAGE Publications, 2023)
This paper delves into the utilisation of Instagram as a platform for self-expression and the establishment of non-normative identities among gender nonconforming Malaysian Muslims. Specifically, the research focuses on Malaysian Muslim males who identify as gender nonconforming and analyse their video posts on Instagram. These individuals construct and manifest their nonconforming identities while navigating the complexities of Malaysian Muslim identity, cultural norms, and religious influences. The deeply rooted Malay identity, combined with the adherence to Islamic principles, presents a challenging conflict for gender nonconforming Malaysians seeking to establish their identities. To address this, many gender nonconforming Malay males adopt the “femeskulin” mode of micro-celebrities on Instagram, blending gender nonconformity with religious values. The findings highlight the potential for coexistence and the significant role played by gender nonconforming individuals in shaping “femeskulin” identity and expression among Malaysian Muslims within the social media platform.